Zoonotic pathogens in the food chain - Hendrick, Stephen; Krause, Denis O. (Wallingford, Oxfordshire : CABI, 2010)
Examining the development, spread and transmission of zoonotic diseases through the food chain; from animals, through production processes to humans, this book discusses the ways modern food production systems contribute to the risk of zoonotic disease,and where mitigation strategies need to be focused. Covering factorsin the animal production process and attributes of microorganisms that allow potential contamination of food sources, this book discusses pathogens that have recently emerged as important infections, and new trends in animal production such as organic livestock farming and raw ..
1. Globalization of the food supply and the spread disease -- 2. Epidemiology of pathogens in the food supply -- 3. Manure as a source of zoonotic pathogens -- 4. Animal feed as a source of zoonotic pathogens -- 5. Milk and raw milk consumption as a vecor for human disease -- 6. The contribution of antibiotic residues and antibiotic resistance genes from livestock operations of antibiotic resistance in the environment and food chain -- 7. On-farm mitigation of enteric pathogens to prevent human disease -- 8. Organic agriculture and its contribution to zoonotic pathogens -- 9. Zoonotic implications of Avian and Swine Influenza -- 10. Crohn's disease in human and Johne's disease in cattle - linked diseases? -- 11. Transmissible Spongiform Encephalopathies as a case study in policy development for zoonoses
Also available in electronic resource
Includes bibliographical references and index
Keywords: Foodborne diseases; Zoonoses